2023
DOI: 10.1172/jci.insight.162060
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor 2 mRNA-binding protein 3 promotes kidney injury by regulating β-catenin signaling

Abstract: Wnt/β-catenin is a developmental signaling that plays a crucial role in driving kidney fibrosis after injury. Activation of β-catenin is presumed to be regulated through the post-translational protein modification. Little is known about whether β-catenin is also subjected to regulation at the posttranscriptional mRNA level. Here, we report that insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3) plays a pivotal role in regulating β-catenin. IGF2BP3 was upregulated in renal tubular epithelium of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Recent studies suggest that IGF2BP3 is a downstream target of Wnt/β‐catenin signaling and plays a key role in renal fibrosis. Knockdown of IGF2BP3 can improve renal fibrosis and inhibit the activation of β‐catenin signaling 13 . Guo et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies suggest that IGF2BP3 is a downstream target of Wnt/β‐catenin signaling and plays a key role in renal fibrosis. Knockdown of IGF2BP3 can improve renal fibrosis and inhibit the activation of β‐catenin signaling 13 . Guo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of IGF2BP3 can improve renal fibrosis and inhibit the activation of βcatenin signaling. 13 Guo et al found that the expression of many Wnt family members and βcatenin increases in a high-glucose environment or the PD effluent of long-term dialysis patients, also accompanied by increased FN expression. 22 This suggests that IGF2BP3 may play an important role in PD-related PF via the Wnt/β-catenin signaling pathway.…”
Section: Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Moreover, research has also focused on the nonnegligible effects of the Wnt/β-catenin and Hedgehog pathways in renal fibrosis. 7,8 Such findings have accelerated the advancement of mechanistic exploration and therapeutic translational research in renal fibrosis. Nevertheless, the complicated mechanisms of renal fibrosis remain unclear, and more intensive research efforts are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored the dual function of transforming growth factor‐β (TGF‐β)/Smad signalling in the course of renal fibrosis 4–6 . Moreover, research has also focused on the nonnegligible effects of the Wnt/β‐catenin and Hedgehog pathways in renal fibrosis 7,8 . Such findings have accelerated the advancement of mechanistic exploration and therapeutic translational research in renal fibrosis.…”
Section: Introductionmentioning
confidence: 99%